Hubungan Kristen-Islam Pasca Tragedi WTC dalam Perspektif Nostra Aetate - In Nugraha Budisantoso (Jurnal Orientasi Baru, 2006)
We have an affectionate formulation about relationship between Christians and Moslems in the declaration of Nostra Aetate on article 3. Rather seen as a conclusion, this formulation is a programmatic vision based on historical experience. It emerged after Christians and Moslems had a long period experience in the way to understand each other and to build togetherness to be ready to and to face the new and dynamic condition of daily life with its progress and challenges. Stimulated by the idea of